The Effectiveness of Logotherapy Counseling with a Dereflection Technique to Improve Broken Home Students Psychological Well-Being - Rachmi, Hanum Isnia; Eddy Wibowo, Mungin; Purwanto, Edy (Universitas Negeri Semarang, 2022)
Disharmony in the parental relationship that leads to a broken home causes poor psychological well-being of students because they are in a stressful condition to adapt to their environment. Therefore, the purpose of this research was to determine the effectiveness of logotherapy counseling with a dereflection technique to improve the psychological well-being of broken home students in tenth grade. It involved 12 students and was done in 5 sessions. Here, an experimental research method with pretest-posttest design was employed, while the data were analyzed using a Wilcoxon analysis. Findings revealed the improvement in the psychological well-being of broken home students after receiving the logotherapy counseling with a dereflection technique. Thus, counselors are suggested to implement logotherapy counseling with a dereflection technique to improve the psychological well-being of broken home students.